2017
DOI: 10.1128/jvi.00461-17
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib and Polycation Combination Treatment Overcomes Multiple Mechanisms of Resistance of Pancreatic Cancer Cells to Oncolytic Vesicular Stomatitis Virus

Abstract: Vesicular stomatitis virus (VSV) is a promising oncolytic virus (OV). Although VSV is effective against a majority of pancreatic ductal adenocarcinoma cell (PDAC) cell lines, some PDAC cell lines are highly resistant to VSV, and the mechanisms of resistance are still unclear. JAK1/2 inhibitors (such as ruxolitinib and JAK inhibitor I) strongly stimulate VSV replication and oncolysis in all resistant cell lines but only partially improve the susceptibility of resistant PDACs to VSV. VSV tumor tropism is general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 86 publications
(118 reference statements)
1
41
0
Order By: Relevance
“…Recently, we demonstrated that the most resistant human PDAC cell line in our study, HPAF-II, showed dramatically weaker attachment of VSV independently of type I IFN signalling [85]. Polycation (polybrene or DEAE-dextran) treatment considerably improved attachment of VSV to HPAF-II.…”
Section: Other Approaches To Improve Vsv Oncoselectivitymentioning
confidence: 51%
See 1 more Smart Citation
“…Recently, we demonstrated that the most resistant human PDAC cell line in our study, HPAF-II, showed dramatically weaker attachment of VSV independently of type I IFN signalling [85]. Polycation (polybrene or DEAE-dextran) treatment considerably improved attachment of VSV to HPAF-II.…”
Section: Other Approaches To Improve Vsv Oncoselectivitymentioning
confidence: 51%
“…Polycation (polybrene or DEAE-dextran) treatment considerably improved attachment of VSV to HPAF-II. Moreover, combining VSV with polycations and ruxolitinib (JAK1/JAK2 inhibitor) successfully broke the resistance of HPAF-II to VSV by concurrently improving VSV attachment and replication [85].…”
Section: Other Approaches To Improve Vsv Oncoselectivitymentioning
confidence: 99%
“…SUIT-2 cells are more resistant to VSV infection in part because of residual type I IFN responses, yet permissive enough to support sufficient viral replication to produce enough viral progeny for continued viral passaging, while MIA PaCa-2 cells are very permissive to VSV infection in part due to their inactive type I IFN signaling (37,41,66). Also, we showed that SUIT-2 cells showed lower levels of VSV attachment, compared to MIA PaCa-2 cells (44). Each virus has a large transgene (about 17% of the WT VSV genome) encoding a different version of p53 fused to RFP.…”
Section: Resultsmentioning
confidence: 72%
“…First, SUIT-2 cells are able to induce a functional type I IFN response to VSV (37,41,66). Second, we observed that, compared to MIA PaCa-2 and some other tested PDAC cell lines, VSV attaches less efficiently to SUIT-2 cells (44). Therefore, we hypothesized that extensive passaging of VSV on SUIT-2 cells selected for spontaneous VSV mutants via the following mechanisms: (i) an improved ability to evade type I IFN signaling and/or (ii) improved attachment to SUIT-2 cells.…”
Section: Vsv-p53-cc (Suit-2) G: M184imentioning
confidence: 76%
See 1 more Smart Citation